2011
DOI: 10.1111/j.1744-7917.2011.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

Niche overlap in allotopic and syntopic populations of sexually interacting ground‐hopper species

Abstract: There is accumulating evidence that sexual interactions among species (reproductive interference) could have dramatic effects for species’ coexistence. It has been shown that the fitness of individuals can be substantially reduced as a consequence of reproductive interference. This might subsequently lead to displacement of a species (sexual exclusion). On the other hand, some evolutionary and ecological mechanisms might enable species to coexist, such as the divergence of mate recognition systems (reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The speciation of different geographic categories was identified by the potential distribution modelling in recent studies. Our study supports the hypothesis that the niche overlap in the sympatric population was greater than that of the allotropic population (Hochkirch & Gröning, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The speciation of different geographic categories was identified by the potential distribution modelling in recent studies. Our study supports the hypothesis that the niche overlap in the sympatric population was greater than that of the allotropic population (Hochkirch & Gröning, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…G.-H. Zhang et al 6 interactions between species and produce different results (Dame & Petren, 2006;Hochkirch & Groning, 2012). Our study shows reproductive interference in laboratory conditions and these two species with the same life history and behavioural traits have the potential for interaction in the field, but further studies are needed to determine if mating interference will occur in field conditions.…”
Section: Discussionmentioning
confidence: 72%
“…Across landscapes, we found examples of behavioural interference influencing the spatial distributions of species in studies ranging in spatial scope from local (<1 km) scales [e.g. Hochkirch & Gröning (2012) found that, within a single nature reserve, reproductive interference causes two groundhopper species to exhibit a mosaic of small‐scale habitat use] to continental (<1000 km) scales [e.g. Reif et al .…”
Section: Systematic Literature Reviewmentioning
confidence: 99%